Role of Calcium Sensing Receptor in Streptozotocin-Induced Diabetic Rats Exposed to Renal Ischemia Reperfusion Injury - Bo Hu; Fei Tong; Long Xu; Zhiwei Shen; Lijian Yan; Guangtao Xu; Ruilin Shen (Karger Publishers, 2018)
Background/Aims: Renal ischemia/reperfusion (I/R) injury (RI/RI) is a common complication of diabetes, and it may be involved in altering intracellular calcium concentrations at its onset, which can result in inflammation, abnormal lipid metabolism, the production of reactive oxygen species (ROS), and nitroso-redox imbalance. The calcium-sensing receptor (CaSR) is a G-protein coupled receptor, however, the functional involvement of CaSR in diabetic RI/ RI remains unclear. The present study was intended to investigate the role of CaSR on RI/RI in diabetes mellitus (DM). Methods: The bilateral renal arteries and veins of streptozotocin (STZ)-induced diabetic rats were subjected to 45-min ischemia followed by 2-h reperfusion with or without R-568 (agonist of CaSR) and NPS-2143 (antagonist of CaSR) at the beginning of I/R procedure. DM without renal I/R rats served as control group. The expressions of CaSR, calmodulin (CaM), and p47phox in the renal tissue were analyzed by qRT-PCR and Western blot. The renal pathomorphology, renal function, oxidative stress, inflammatory response, and calcium disorder were evaluated by detection of a series of indices by hematoxylin-eosin (HE) staining, transmission electron microscope (TEM), commercial kits, enzyme-linked immunosorbent assay (ELISA), and spectrophotofluorometry, respectively. Results: Results showed that the expressions of CaSR, CaM, and p47phox in I/R group were significantly up-regulated as compared with those in DM group, which were accompanied by renal tissue injury, increased calcium, oxidative stress, inflammation, and nitroso-redox imbalance. Conclusion: These results suggest that activation of CaSR is involved in the induction of damage of renal tubular epithelial cell during diabetic RI/RI, resulting in lipid peroxidation, inflammatory response, nitroso-redox imbalance, and apoptosis.